Risk factors associated with hypertensive disorders of pregnancy within an urban indigenous population in south western Sydney. Issue 3 (6th March 2018) - Daly, Amy L.; Sriram, Nina; Woodall, Cheryl; Selvakumar, Kierrtana; Briggs, Kelly; Garg, Parul; Russell, Lisa; Yu, Michelle; Beetson, Karen; Hennessy, Annemarie; ,
Abstract: Background: The prevalence of hypertensive disorders of pregnancy (HDP) in Australia's urban indigenous women is unknown. Aim: To explore the risk factors associated with HDP for a cohort of urban indigenous women in South‐Western Sydney, Australia. Methods: This study was conducted in partnership with the Tharawal Aboriginal Medical Service. Women (18–45 years) were recruited at the clinic and community events. The quantitative questionnaire included obstetric history, personal and family history of hypertension. Anthropometric measurements and blood pressure were conducted. Rates were compared with Australian Bureau of Statistics (ABS) national rates. Results: Eighty‐three participants completed the questionnaire. The rate of ever having HDP in a pregnancy was 36.1%. The overall ABS rate was 9.8% and for indigenous women, 14%. The mean maternal age at first pregnancy was 20.8 years (SD 3.7 years). The mean body mass index (BMI) of the sample population ( n = 81) was 32.2 kg/m 2 (SD 9.5 kg/m 2 ) and BMI was not related to HDP ( P = 0.197). Of those questioned, 25.3% had an individual history and 63.9% had a family history of hypertension. The effect of family history of hypertension ( P = 0.020) (odds ratio (OR) 4.29; 95% confidence interval (CI); 1.42–12.93) and individual history of hypertension ( P < 0.001) (OR 15.69; 95% CI; 4.50–54.76) were associated with HDP. Conclusion: There was a higher rate of HDP in urban indigenous women compared to the national indigenous prevalence. The family history, or individual history of hypertension was the most significant risk factors and BMI was not identified as a risk factor for HDP in this population.